Deep Transfer Learning Networks for Brain Tumor Detection: The Effect of MRI Patient Image Augmentation Methods - Abdalla, Peshraw Ahmed; Qadir, Abdalbasit Mohammed; Rashid, Omed Jamal; Rawf, Karwan M. Hama; Abdulrahman, Ayub O; Mohammed, Bashdar Abdalrahman (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
The exponential growth of deep learning networks has enabled us to handle difficult tasks, even in the complex field of medicine with small datasets. In the sphere of treatment, they are particularly significant. To identify brain tumors, this research examines how three deep learning networks are affected by conventional data augmentation methods, including MobileNetV2, VGG19, and DenseNet201. The findings showed that before and after utilizing approaches, picture augmentation schemes significantly affected the networks. The accuracy of MobileNetV2, which was originally 85.33 percent, was then enhanced to 96.88 percent. The accuracy of VGG19, which was 77.33 percent, was then enhanced to 95.31 percent, and DenseNet201, which was originally 82.66 percent, was then enhanced to 93.75 percent. The models' accuracy percentage engagement change is 13.53 percent, 23.25 percent, and 23.25 percent, respectively. Finally, the conclusion showed that applying data augmentation approaches improves performance, producing models far better than those trained from scratch.